High-dose chemoradiotherapy and watchful waiting for distal rectal cancer: a prospective observational study. Issue 8 (August 2015) - Appelt, Ane L; Pløen, John; Harling, Henrik; Jensen, Frank S; Jensen, Lars H; Jørgensen, Jens C R; Lindebjerg, Jan; Rafaelsen, Søren R; Jakobsen, Anders
Summary: Background: Abdominoperineal resection is the standard treatment for patients with distal T2 or T3 rectal cancers; however, the procedure is extensive and mutilating, and alternative treatment strategies are being investigated. We did a prospective observational trial to assess whether high-dose radiotherapy with concomitant chemotherapy followed by observation (watchful waiting) was successful for non-surgical management of low rectal cancer. Methods: Patients with primary, resectable, T2 or T3, N0–N1 adenocarcinoma in the lower 6 cm of the rectum were given chemoradiotherapy (60 Gy in 30 fractions to tumour, 50 Gy in 30 fractions to elective lymph node volumes, 5 Gy endorectal brachytherapy boost, and oral tegafur-uracil 300 mg/m 2 ) every weekday for 6 weeks. Endoscopies and biopsies of the tumour were done at baseline, throughout the course of treatment (weeks 2, 4, and 6), and 6 weeks after the end of treatment. We allocated patients with complete clinical tumour regression, negative tumour site biopsies, and no nodal or distant metastases on CT and MRI 6 weeks after treatment to the observation group (watchful waiting). We referred all other patients to standard surgery. Patients under observation were followed up closely with endoscopies and selected-site biopsies, with surgical resection given for local recurrence. The primary endpoint was local tumour recurrence 1 year after allocation to the observation group. This study is registered withClinicalTrials.gov, numberNCT00952926 . Enrolment is closed, but follow-up continues for secondary endpoints. Findings: Between Oct 20, 2009, and Dec 23, 2013, we enrolled 55 patients. Patients were recruited from three surgical units throughout Denmark and treated in one tertiary cancer centre (Vejle Hospital, Vejle, Denmark). Of 51 patients who were eligible, 40 had clinical complete response and were allocated to observation. Median follow-up for local recurrence in the observation group was 23·9 months (IQR 15·3–31·0). Local recurrence in the observation group at 1 year was 15·5% (95% CI 3·3–26·3). The most common acute grade 3 adverse event during treatment was diarrhoea, which affected four (8%) of 51 patients. Sphincter function in the observation group was excellent, with 18 (72%) of 25 patients at 1 year and 11 (69%) of 16 patients at 2 years reporting no faecal incontinence at all and a median Jorge-Wexner score of 0 (IQR 0–0) at all timepoints. The most common late toxicity was bleeding from the rectal mucosa; grade 3 bleeding was reported in two (7%) in 30 patients at 1 year and one (6%) of 17 patients at 2 years. There were no unexpected serious adverse reactions or treatment-related deaths. Interpretation: High-dose chemoradiotherapy and watchful waiting might be a safe alternative to abdominoperineal resection for patients with distal rectal cancer. Funding: CIRRO—The Lundbeck Foundation Center for Interventional Research in Radiation Oncology and The Danish Council for Strategic Research.